Mapping Trends and Insights in Islamic Sustainable Finance: A Bibliometric Analysis - Kholidah, Himmatul; Hijriah, Hanifiyah Yuliatul; Fadhlillah, Hanif (e-Journal Ekonomi Bisnis dan Akuntansi, 2025)
Islamic sustainable finance has increasingly garnered attention in academic discussions, specifically for tackling key ecological, social, and governance (ESG) challenges. This study uses VOSviewer and Biblioshiny software for bibliometric analysis to analyze all 200 scholarly articles and identify main trends, contributors and research gaps. The number of research outputs increased noticeably after 2020, when green sukuk and effect investing became emerging themes. Research on other Islamic financial instruments, waqf-based financing, and Takaful remains underexplored. The results of this study show that Islamic sustainable finance can become transparent and effective using blockchain with fintech among other technical improvements. Further research is still needed to understand how this technology can be utilized. Co-authorship analysis shows that research is still fragmented. The top three countries are Malaysia, Indonesia, and Saudi Arabia. Countries need further collaboration not only for knowledge sharing but also for aligning rules. Although much theoretical discussion has taken place, few empirical studies have measured the actual impact of Islamic sustainable finance on economic, social, and ecological outcomes. This research highlights the need for further research on public awareness and adoption, with a particular focus on behavioral factors affecting investment decisions. The regulatory frameworks for Islamic sustainable finance are still evolving and developing steadily, and a standard global approach is yet to be achieved. Future research can do better by collecting more data, experimenting to test ideas, and collaborating across fields.